Factors protecting Swiss nurses' health during the COVID-19 pandemic: a longitudinal study - Jonathan Jubin; Philippe Delmas; Ingrid Gilles; Annie Oulevey Bachmann; Claudia Ortoleva Bucher (BMC, 2023)
Abstract Background The COVID-19 pandemic reached Europe in early 2020 and impacted nurses over a prolonged period, notably causing heavy work overloads. Exposure to sources of stress in such situations is inevitable, which can put nurses' health at risk. The present study took a salutogenic approach to investigating nurses' health and the principal factors protecting it found in the literature (i.e., resilience, post-traumatic growth, social support, and certain organizational factors), as well as how those elements evolved from February 2021 to September 2022. Methods All nurses working at eight French-speaking Swiss hospitals who accepted to disseminate the study to their employees were invited to complete an online questionnaire at four time points (February 2021, September 2021, March 2022, and September 2022: T0, T1, T2, and T3, respectively) and respond to items measuring their health, factors protecting their health, and their perceived stress levels. Data were analyzed using random-intercept linear regression models. Results A cumulated total of 1013 responses were collected over all measurement points (625 responses at T0; 153 at T1; 146 at T2; 89 at T3). Results revealed that nurses' health had not changed significantly between measurements. However, their perceived stress levels, feelings of being supported by their management hierarchies, and belief that they had the means to deliver a high quality of work all diminished. At every measurement point, nurses' health was negatively associated with perceived stress and positively associated with resilience, perceived social support, and the belief that they were provided with the means to deliver a high quality of work. Conclusion Despite the difficult conditions caused by the pandemic, the factors recognized as protective of nurses' health played their role. The lack of improvements in nurses' health in periods when the pandemic's effects lessened suggests that the pressure they were experiencing did not drop during these moments. This phenomenon may have been due to the need to clear backlogs in scheduled surgery and the work overloads caused by prolonged staff absences and nurses quitting the profession. Monitoring changes in nurses' health is thus crucial, as is establishing measures that promote factors protective of their health. Organizational factors influencing nurses' working conditions are also key and should not be neglected.